Actualization of Religious Culture in Improving Student Discipline - M Aliyul Wafa; Ninik Lailatul Husna; Khoirun Nisa' (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Education is not only limited to the development of human intellectuality, meaning that it does not only increase intelligence, but also develops all aspects of human personality, one of which is discipline. In forming a disciplined student personality, rules or regulations are needed which become the culture in the school. Therefore, this study aims to obtain empirical evidence regarding the Actualization of Religious Culture in Improving Student Discipline at Madratsah Tsanawiyah Negeri 2 Jombang. This research is expected to be used as material for school considerations to establish religious culture as an effort to improve student discipline, and the results of this study can add to the literature and can be used as reference material for further research. The research method used is descriptive qualitative analysis. Data collection used was interviews, observation and documentation. Data collection in the field was carried out in 2021. The results showed that the actualization of religious culture in Madratsah Tsanawiyah 2 Jombang was effective and efficient in improving student discipline. With supporting factors in the form of habituation to obey the rules and penalties for violators.